Principles and strategies of teaching - Corpuz, Brenda B.; Salandanan, Gloria G. (Quezon City, Philippines : Lorimar Publishing Company Inc., 2003)
This book contains the precipitate of a number of years of teaching the course, Principles and Methods of teaching. It translate the latest findings of educational research and most recent educational theories into classroom practice.
Unit 1. Principles of teaching -- Unit 2. Teaching strategies -- Unit 3. Instructional Planning -- Unit 4. Developing a lesson -- Unit 5. Art of questioning -- Unit 6. Building effective schools.
Includes bibliographical references.
Keywords: TEACHING